2016
DOI: 10.3126/jssn.v17i1.15179
|View full text |Cite
|
Sign up to set email alerts
|

Change in storage symptoms after transurethral resection of prostate: a prospective observational study

Abstract: Introduction: Patients with enlarged prostate generally rate their storage symptoms (frequency, urgency and nocturia) as the most bothersome as these symptoms interfere more with daily activities and have huge impact on quality of life. Effect of transurethral resection of prostate (TURP) on storage symptoms is unknown. Objective of the study is to assess the change in storage symptoms in patients undergoing TURP.Methods: A prospective observational study was conducted at the author’s institute from August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The mean preoperative IPSS and QOL scores in the non-catheterized group were 25.70 and 5.72, respectively, which was similar to the findings by Luitel et al but higher than reported by Choi et al [ 15 , 26 ]. The higher IPSS score may be due to the delayed presentation of our patients to seek care after the symptoms were significantly bothersome.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The mean preoperative IPSS and QOL scores in the non-catheterized group were 25.70 and 5.72, respectively, which was similar to the findings by Luitel et al but higher than reported by Choi et al [ 15 , 26 ]. The higher IPSS score may be due to the delayed presentation of our patients to seek care after the symptoms were significantly bothersome.…”
Section: Discussionsupporting
confidence: 87%
“…However, there was no significant difference with regard to complications higher than Clavien II. The improvement in complication rate in recent studies can be attributed to the advancements in surgical technique and technology related to the instrument's design [ 13 , 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean values of some components increased significantly after TURP surgery, but no significant changes occurred in the symptoms of nocturia before and after surgery, with the conclusion that the ratio of improvement of nocturia to 7 symptoms of LUTS was the lowest 14 . Likewise, Luitel Gupat examined the results of post TURP surgery after 3 months showing a significant decrease in IPSS scores, symptoms of voiding that were better than storage symptoms but storage symptoms were unlikely to return to normal 15 . Naoki Wada's research in 2012 stated that nocturia is one of the most annoying symptoms of LUTS for patients and is the most difficult to treat because the disease that causes nocturia varies from urological conditions to non-urological conditions.…”
Section: Introductionmentioning
confidence: 99%